The role of health, experience, and educational attainment in agricultural production: Evidence from smallholders in Burkina Faso - Wouterse, Fleur Stephanie; Badiane, Ousmane (Wiley, 2019)
We apply parametric and nonparametric methods to data from smallholders in Burkina Faso and assess the role that human capital characteristics play in the agricultural production process. Our results point to the technology‐changing nature of health, education, and experience. However, effects are rather heterogeneous. The productivity elasticity of health is much larger for households in the lowest landholding quintiles, while returns to experience are larger for households in the upper quintile. In terms of policy implications, our results suggest that productivity can be stimulated through the allocation of expenditure to social services that enhance certain types of human capital. Interventions aimed at improving the health status of households with smaller landholdings could have particularly strong welfare effects.